Da ideia à forma. A Faculdade de Arquitectura da Universidade do Porto como caso de estudo - Carla Sofia Cruz da Rocha Viana (2010)
When talking of Architecture it is inevitable to approach the theme of form. But forms, as they appear to us, are the result of a group of reflections and ideals, which on their turn determin a specific approach to architecture itself. Not only on materialization, as the final result that mediates the relationship between Man and his Space, but mostly during the design process form allows the pre-visualization necessary for the decision making that supports the project development. Besides reducing the subjectivity present in architectural considerations, to search the underlying reasons to a determined formal composition implicates an approach to the basis of the discipline, having always as a goal to consolidate quality parameters capable of attributing greater atemporality through persisting form. This way, having as purpose the consolidation of an understanding of formal production, the present investigation wishes to, through the analysis of the Faculty of Architecture of the University of Oporto, by Siza Vieira, expose a determined approach to architectural procedure, same to say of its forms, which is based on the permanent discussion around architecture. Between abstract or concrete components, the knowledge of history and the consideration of present, the moments of formal achievement are always moments of evaluation and choice, in which the authors sensitivity and education undertake a decisive role. Supported by the procedural and formal analysis of the study case, one is able to individualize the heteronym character - of contingence towards the circumstantial factors - and autonomous character - abstraction of the subject from the adjacent circumstances, being guided by composition coordinates - ultimately searching for the underlying design idea capable of attributing hierarchy to the group of parameters and relations that materialize into form. The Faculty of Architecture of the University of Oporto reveals with excellence that realizing the importance of the formal component itself is as important as to condition it to external factors, just as long the architect, through the design idea and with a strong sense of responsibility, is able to overcome his greatest challenge: translate into form a way of thinking architecture.